Sodium Content in Vegetable Soups Prepared Outside the Home: Identifying the Problem - Carla Goncalves (2012)
Cardiovascular diseases are a major cause of mortality and disability in developed countries, accounting for 39% of deaths. One of the most important factors associated with their onset is a high sodium intake, which increases the risk of high blood pressure. Excessive salt intake is associated with the consumption of processed foods and eating outside home, which nowadays can vary from one to all day meals. The consumption of vegetable soup is a healthy cultural practice, negatively associated with obesity, but their high sodium levels raised some concern recently. The aim of this work was to quantify the sodium content in vegetable soups served at public institutions' canteens. Soups, with and without salt added, were collected from kindergartens, elementary schools and nursing homes, and their sodium content was determined by flame photometry. In soups without added salt, sodium contents ranged from 0.13 to 216.63 mg/100g, in nursing homes, and 0.93 to 284.02 mg/100g, in kindergartens. Sodium content in soups with added salt ranged from 124.71 to 429.04 mg/100g, in nursing homes, from 36.58 to 409.53 mg /100g, in elementary schools, and from 63.23 to 438 mg/100g, in kindergartens. Considering a standard serving of 300g, sodium intake reported from soup alone can represent 31 to 54% of the adequate daily intake, becoming a major contributor to the high sodium intakes reported in developed countries. As most of the sodium comes from added salt during cooking processes, intervention strategies should be directed to raise awareness among food handlers and chefs about limiting salt content in different foods, as well as educational strategies directed for the consumer, in order to maintain acceptability of soups with reduced sodium content.